Emblematic and material color in the Paracas-Nasca Transition - Ann H. Peters (Nuevo mundo - Mundos Nuevos, 2016)
Emblematic and esoteric uses of color combinations have been proposed for Paracas Necrópolis textiles, since their first analysis in 1930 by Rebeca Carrión. While other scholars also have traced patterns of color variation among the figures repeated on large mantles, Anne Paul has contributed thorough documentation and has traced the distribution of other artifact types and design features among the gravelots. I seek to complement Paul’s work by tracing the combination of dominant color fields that communicate at great distance, and considering the interplay between the highly visible contrasts of background fields, the layers of patterned variability perceived upon approach, and the nearly invisible messages of interlace structures and yarn composition. While most previous studies have concentrated on late, Nasca-related textile assemblages, I focus on the early mortuary bundles and the relationship between textiles associated with the Topará and Paracas ceramic traditions. Comparison of predominant and exceptional styles in each Wari Kayan mortuary context with those of textiles from contemporary Ocucaje tombs reveals color schemes that indicate social identities and exchange relationships expressed in mortuary ritual.